(untitled) (Proceeding of Dakwah Saizu International Conference, 2023)
Da’wah currently has a significant shift. This article discusses the branding and packaging strategy of da’wah carried out by the Pola Pertolongan Allah /Allah Assistance Pattern (PPA) Institute for young urban Muslim mothers in the form of the Spiritual Motherhood class. Based on research conducted in 2022 and 2023, this paper tries to reveal a shift in the pattern of preaching carried out by the PPA Institute in the Spiritual Motherhood class towards hybrid preaching. The author uses a qualitative method with a netnographic approach to uncover da’wah activities and their marketing in online media, interviews with key informants and observations. This research found that the Spiritual Motherhood class is intended to appreciate and serve the hopes and desires of young urban Muslim mothers to become pious women and good mothers. The manifestation of this appreciation is the packaging of da’wah in the form of classes and training with interesting themes and planned times, which are carried out offline and online. The strategy of packaging da’wah and marketing has attracted Muslim women from various backgrounds to participate even though they have to pay a high fee. This phenomenon shows that the PPA Institute’s preaching activities lead to hybrid preaching. The hybridity of da’wah in the spiritual motherhood class can be seen in four ways, namely the pattern of da’wah communication in the form of offline and online training and healing classes, the diversity of congregations that transcend the boundaries of place, culture and ideology, and the shift of da’wah towards the religious market where the spiritual motherhood class PPA Institute is offered like a market commodity. The participants followed his da’wah with rational considerations. The media has an important role in the success of the Motherhood Spiritual class